MODEL CEGAH TANGKAL TINDAK KORUPSI - Tjiptogoro Dinarjo Soehari; Iffah Budiningsih (Akademika, 2016)
Transparency International has issued the corruption ranks for 2015 and Indonesia sits in 107positions, much better than the previous year position, which was in 114 positions of 174 investigatedcountries. However, this position is still far below Philippine, Thailand, Malaysia, and Singapore whosits in the thirties ranks. The efforts to eradicate corruption have been done through legal approach,building awareness and community participation through Corruption Eradication Commission (KPK)and other institutions. Regardless, the corruption index is still high. This shows that the efforts thatcurrently implemented tend to be less effective. Hence, other alternatives, such as, strategic humanresource management needs to be looked at to optimize the community participation to prevent anddeter corruption. Further, this effort is expected to curb the number of corruption cases in Indonesia.The purpose of this research is to develop a model to build effective institutions internal environmentand healthy so it can hit as low as possible the occurrence of acts of corruption.This research uses explorative quantitative survey method, meanwhile, descriptive andregression analyses are used in data analysis. The dependent variable is the prevention and deterrenceof corruption (Y), whereas, the independent variables are organizational culture (X1), Competencies(X2), Leadership (X3), and Internal Monitoring (X4). The population of this research is the employeesat the Joglo village office of Kemanggisan sub-district, West Jakarta City. The total number ofpopulation is 25 people, which is also the total sample.The conclusions of this research are, among others: a) The regression model of corruption preventionand deterrence is Y = 4,94 + 6,08x1 – 0,155X2 – 0,058X3 + 0,176X4; b) organizational culture effectsignificantly to prevent acts of corruption and charms has the greatest influence among other freevariables so it should be a priority in the policy prohibit acts of corruption charms; c) competencieshave a negative effect against barring acts of corruption but the charms not significant so that it doesnot include priority in building barring corruption acts of charms. Smart, savvy employees are criticalbut would damage the organization when no mandate; d) influential leadership negatively to preventacts of corruption but the charms not significant so that it does not include prioritaas in building barringcorruption acts of charms; e) internal monitoring positive effect against barring acts of corruption butcharms the level of its influence under the organizational culture, so although not including priority inbuilding barring acts of corruption, but charms the need developed an internal system of control whichis associated with the culture of the organization